Evaluation of the cytotoxic and mutagenic potential of Rosmarinus officinalis L. essential oil through the Allium cepa Leach bioassay (Acta Scientiarum. Biological Sciences, 2022)
The species Rosmarinus officinalis L. (rosemary) is an herb from the Lamiaceae family, widely used in cooking as a food preservative, seasoning or condiment. It also stands out for its therapeutic properties, mainly presenting antioxidant, antibacterial and antitumor activity. The aim of this study was to evaluate the cytotoxic and mutagenic activity of R. officinalis L. essential oil through the Allium cepa bioassay. This test constitutes an excellent plant model routinely used due to its sensitivity, low cost and good correlation with test systems in mammals. The defined concentrations for carrying out the test were 750, 243, 81 and 27 µg mL-1. Five bulbs were used, 4 roots of each, measuring approximately 2 cm, and they were analyzed on two slides. All assays were performed at least in triplicate and compared to the negative control. The statistical test of analysis of variance (ANOVA with a fixed factor) was used, followed by Tukey's multiple comparisons test, for p < 0.05. For this purpose, the GraphPad Prism program (version 6.0) was used. The results showed a cytotoxic and mutagenic effect for all concentrations used of the essential oil of R. officinalis L. However, it is important to conduct further research using other genotoxicological tests with different endpoints and at different concentrations, in order to clarify the interaction of the essential oil of the species R. officinalis L. with the genetic material of the cell and its possible mechanism of action.